Rh, Ir, and Ru Partitioning in the Cu-Poor IPGE Massive Ores, Talnakh Intrusion, Skalisty Mine, Russia - Nadezhda Tolstykh; Valeriya Brovchenko; Viktor Rad’ko; Maria Shapovalova; Vera Abramova; Jonathan Garcia (Minerals, 2021)
Pyrrhotite (or Cu-poor) massive ores of the Skalisty mine located in Siberia, Russia, are unique in terms of their geochemical features. These ores are Ni-rich with Ni/Cu ratios in the range 1.3–1.9 and contain up to 12.25 ppm Ir + Rh + Ru in bulk composition, one of the highest IPGE contents for the Norilsk–Talnakh ore camp. The reasons behind such significant IPGE Contents cannot simply be explained by the influence of discrete platinum-group minerals on the final bulk composition of IPGE because only inclusions of Pd minerals such as menshikovite, majakite, and mertieite II in Pd-maucherite were observed. According to LA-ICP-MS data obtained, base metal sulfides such as pyrrhotite, pentlandite, and pyrite contain IPGE as the trace elements. The most significant IPGE concentrator being Py, which occurs only in the least fractionated ores, and contains Os up to 4.8 ppm, Ir about 6.9 ppm, Ru about 38.3 ppm, Rh about 36 ppm, and Pt about 62.6 ppm. High IPGE contents in the sulfide melt may be due to high degrees of partial melting of the mantle, interaction with several low-grade IPGE impulses of magma, and (or) fractionation of the sulfide melt in the magma chamber.